If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x = -12 + 10x Solving 13x = -12 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13x + -10x = -12 + 10x + -10x Combine like terms: 13x + -10x = 3x 3x = -12 + 10x + -10x Combine like terms: 10x + -10x = 0 3x = -12 + 0 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| d+2.7t=-4.8t-6 | | 5v^2=35v | | 4x+8x=9-5x | | x^3-21x^2+33x-243=0 | | 7-20=6x-5-5x | | [m+4]+4=14 | | 12=3x-16 | | y^2-12y+36=100 | | 8+10x+2x=3+12x | | [m+4]+6=24 | | 5t+11=7t-15 | | 4x+8=2(x+6) | | 9y-3=6y+6 | | 147-6x=30x+19 | | 42-4t=12+6t | | -116x-7x=7x+24 | | 3(-4x+8)+3x-4(2x-5)=5x | | 9+2x=6(x+3)-5(x-1) | | 3c=-12 | | 3c=-112 | | 16x-3x^2=184 | | f(x)=x^2+10x+17 | | (8x+5/4)(8x-1/4) | | 18+21x= | | 211-2x=43x+31 | | 9T^2+4T=0 | | (5x+1)(4x^2+4x+7)= | | Y=400+0.75Y-10r | | 15x-206=6x-8 | | 25x-5y=750 | | 69-2x=7x+21 | | 20y+16=18y-9 |